Failing mouse hearts utilize energy inefficiently and benefit from improved coupling of glycolysis and glucose oxidation. (17th September 2013) - Masoud, Waleed G.T.; Ussher, John R.; Wang, Wei; Jaswal, Jagdip S.; Wagg, Cory S.; Dyck, Jason R.; Lygate, Craig A.; Neubauer, Stefan; Clanachan, Alexander S.; Lopaschuk, Gary D.
Abstract: Aims: To determine whether post-infarction LV dysfunction is due to low energy availability or inefficient energy utilization, we compared energy metabolism in normal and failing hearts. We also studied whether improved coupling of glycolysis and glucose oxidation by knockout of malonyl CoA decarboxylase (MCD-KO) would have beneficial effects on LV function and efficiency. Methods and results: Male C57BL/6 mice were subjected to coronary artery ligation (CAL) or sham operation (SHAM) procedure. After 4 weeks and echocardiographic evaluation, hearts were perfused (working mode) to measure LV function and rates of energy metabolism. Similar protocols using MCD-KO mice and wild-type (WT) littermates were used to assess consequences of MCD deficiency. Relative to SHAM, CAL hearts had impaired LV function [lower % ejection fraction (%EF, 49%) and LV work (46%)]. CAL hearts had higher rates (expressed per LV work) of glycolysis, glucose oxidation, and proton production. LV work per ATP production from exogenous sources was lower in CAL hearts, indicative of inefficient exogenous energy substrate utilization. Fatty acid oxidation rates, ATP, creatine, and creatine phosphate contents were unaffected. Utilization of endogenous substrates, triacylglycerol and glycogen, was similar in CAL and SHAM hearts. MCD-KO CAL hearts had 31% higher %EF compared with that of WT-CAL, and lower rates of glycolysis, glucose oxidation, proton production, and ATP production, indicative of improved efficiency. Conclusion: CAL hearts are inefficient in utilizing energy for mechanical function, possibly due to higher proton production arising from mismatched glycolysis and glucose oxidation. MCD deficiency lessens proton production, LV dysfunction, and inefficiency of exogenous energy substrate utilization.